(3GdMSjfjI aj GdBOGHs - (3GdCfWGcj, MSjf Hf YHO Gddg, J (B1130 (3g`s
(3ChdgG (B:s
(3EPG bdJ Hcde aEf cfJ fGbdG ajg Ch eOYjG aGdhXGFa GdehLgI ef GdNUe GdefGbVI eLGR dZhjG eWdbGs
(3BNQgG (B:s
,, (3hEKHGJgG HEHWGd GdTGgO hJMQjQ GdeYQha hELRGA GdJYQja eGOI fbVg aj GdKdGKI GdCNjQI haj GdeagheGJ GdMbjbjI ceG aj GdGYJHGQjI aj GdKdGKI GdCNjQIs
(3aj Chdg fbhd aj GddZI hGdMSGH HNW CHj GdSYhOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1 / 617s
(3gOjI GdYGQajf (B1/ 325s
(3EjVGM Gdecfhf (B1/ 406s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs